Are They too Old to Learn? : Exploring the Barriers to using Weblogs in Demystifying the Information Literacy Experience for Mature Age Undergraduate Students - Anastasi, Jenny; Cochrane, Sandra (Proceedings of the International Conference on Networked Learning, 2006)
Active engagement with Weblogs by students presents an enticing new dimension in e.learning. Much of the current literature would suggest that embracing blogs appears, primarily, to be an activity of the young. This paper reports on findings from a survey that explored the blogging behaviours of mature age (23+ years), undergraduate students undertaking first year courses across a number of disciplines at an Australian regional University as part of a broader study. The researchers were keen to develop an understanding of Weblog usage from the learner’s perspective. The study was able to identify some of the barriers that prevented this cohort of students from actively engaging in Weblog interaction. The findings from this study will inform the development of programs aimed at facilitating information literacy skills in students new to study at the university.